Bioactive properties of fermented donkey milk, before and after in vitro simulated gastrointestinal digestion - Aspri, Maria; Leni, Giulia; Galaverna, Gianni; Papademas, Photis (My University, 2018)
Indigenous strains of lactic acid bacteria previously isolated from raw donkey milk samples were used to ferment donkey milk. Each sample was subjected to an in vitro simulated gastrointestinal digestion (SGID) and analysis of the digesta by HPLC-LTQ-Orbitrap XL was performed in order to obtain a comprehensive peptide profile of fermented donkey milk. Functional properties such as ACE-inhibitory, antimicrobial and antioxidant activities of the resulting fermented donkey milks, as well as characterization of the bioactive peptides produced by an in vitro SGID, were assayed. All bioactivities were found to be high in fermented milk and a further significant increase was observed after SGID. The Enterococcus faecium DM33 fermented milk exhibited the strongest antioxidant and the highest antimicrobial activities. The highest ACE-inhibitory activity was observed in milk fermented with Lactobacillus casei DM214. These findings will contribute to the development of a new functional dairy drink with anti-hypertensive, antimicrobial and/or antioxidant activities.
Keywords: ACE-activity; Antimicrobial; Antioxidant; Bioactivity; Digestion; Donkey milk; Fermentation; Gastrointestinal